1995
DOI: 10.3354/meps122073
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the spatio-temporal occurrence of fish eggs and larvae in a northern, physically dynamic coastal environment

Abstract: Distribution patterns, abundance and species composition of the assemblages of fish eggs and larvae in Conception Bay, Newfoundland. Canada. during the early summers of 1990 and 1991 are described. Several species appear to use Conception Bay as a spawning ground. lnterannual and seasonal differences in both species composition and abundance in the bay appear to be associated with differences in environmental conditions, particularly with temperature. Both egg and larval abundances were lower by an order of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 14 publications
3
32
0
2
Order By: Relevance
“…temperature, salinity, integrated fluorescence) were calculated for three distinct water column layers (Laprise and Pepin, 1995) (Fig. 2B): The layer immediately below the sea-surface down to the depth where the temperature was 1°C less than that of the surface waters, was defined as the 'surface mixed layer' (SML).…”
Section: Discussionmentioning
confidence: 99%
“…temperature, salinity, integrated fluorescence) were calculated for three distinct water column layers (Laprise and Pepin, 1995) (Fig. 2B): The layer immediately below the sea-surface down to the depth where the temperature was 1°C less than that of the surface waters, was defined as the 'surface mixed layer' (SML).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of spawning site and hydrographic conditions plays an important role in the determination of larval drift or transport (Heath 1989, Laprise & Pepin 1995. Most of the dispersive drift from the spawning grounds of herring stocks in western European waters is in an easterly direction , although other studies have suggested that retention of larvae is important for recruitment success (Iles & Sinclair 1982, Sinclair & Tremblay 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse environmental conditions in nature can be the cause of significant embryonic mortality (Laprise and Pepin, 1995). Sub-lethal environmental stress impacts on all aspects of development, including myogenesis, with potential consequences for the morphology, physiology, behaviour and survival of the hatched larvae.…”
Section: Plasticity Of Myogenesis In Early Life Stages Temperaturementioning
confidence: 99%